2015
DOI: 10.1186/s13643-015-0001-y
|View full text |Cite
|
Sign up to set email alerts
|

The safety and efficacy of vortioxetine for acute treatment of major depressive disorder: a systematic review and meta-analysis

Abstract: BackgroundVortioxetine is the first mixed serotonin agonist and antagonist antidepressant approved in the US. We sought to evaluate all published and unpublished data available to determine the efficacy and harms of vortioxetine in adults with major depressive disorder.MethodsWe used a predefined search strategy of MEDLINE, the Cochrane Central Register of Controlled Trials, ClinicalTrials.gov, and Drugs@FDA to identify studies evaluating vortioxetine in the acute treatment of major depressive disorder. Only r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 22 publications
(21 reference statements)
3
19
0
Order By: Relevance
“…vortioxetine, vilazodone and levomilnacipran) remain limited. Nevertheless, similarly to other antidepressant agents, nausea was one of the most frequently reported side effects [38,39,40]. …”
Section: Gastrointestinalmentioning
confidence: 99%
“…vortioxetine, vilazodone and levomilnacipran) remain limited. Nevertheless, similarly to other antidepressant agents, nausea was one of the most frequently reported side effects [38,39,40]. …”
Section: Gastrointestinalmentioning
confidence: 99%
“…Thus, in addition to difficulties in concentration, problems in decision making were recently specified within the diagnostic criteria of depression [9].Our case exemplifies the existence of cognitive deficits in depression regardless of cardinal humor symptoms. Recently, medications such as vortioxetine have been designed to treat both spheres of depression: cognition and mood [10][11][12]. However, the commercialization of this drug only began to be performed in Brazil in early 2016, that is after the treatment reported in this article.…”
Section: Discussionmentioning
confidence: 99%
“…A second meta-analysis (11 studies, 6,145 participants) showed that, compared with placebo, response rates were significantly higher with vortioxetine 5mg (relative risk [RR] 1.3, 95% CI 1.1 to 1.6), 10mg (RR 1.4, 95% CI 1.2 to 1.7) and 20mg (RR 1.6, 95% CI 1.2 to 2.1) but not with 15mg, and did not significantly increase with increasing dose 20. Compared with placebo, remission rates were higher with 10mg (RR 1.5, 95% CI 1.2 to 1.8) and 20mg doses (RR 1.7, 95% CI 1.2 to 2.4), but not with 5mg or 15mg.…”
Section: About Vortioxetinementioning
confidence: 99%